Friesodielsia sahyadrica (Annonaceae), a peculiar new species from the Western Ghats, India - Page, Navendu V.; Surveswaran, Siddharthan (Phytotaxa, 2014)
Annonaceae are one of the largest families of the magnoliid angiosperms, comprising trees, shrubs and lianas. Although they exhibit a pantropical distribution, relatively high levels of generic endemism are observed at the continental scale (Doyle and Le Thomas 1997). In India, they are represented by 24 genera and ca. 125 species (Kundu 2006).